Modeling for PWM Voltage Source Converter Controlled Power Transfer - Douangsyla, S.; Indarack, P.; Kanthee, A.; Kando, M.; Kittiratsatcha, S.; Kinnares, V. (My University, 2004)
In this paper, a model for PWM Voltage Source Converter (VSC) Controlled Power Transfer has been developed. A vector control strategy with PI controllers is proposed. This paper studied the PWM Voltage Source Converter connected to an active ac network with vector control strategy. PWM pattern generation is based on a carrier technique. The instantaneous 3-phase voltages and currents are transformed to a 2-axis (d-q) reference frame system [1] which rotates at the supply angular frequency (ωe). Thus it is possible to have decoupled control of the active (P) and reactive (Q) power flow and it is necessary to develop a mathematical model for VSC to determine controlling variables. The design and the performance of controllers are investigated. Digital simulation shows the feasibility of the proposed control strategy.